Genotyping of Helicobacter Pylori Isolated From Iraqi Patient with Upper Gastrointestinal Disease - Aseel H. Al-Sabary (Journal of Global Pharma Technology, 2017)
H. pyloriis one of the most frequent pathogen infected about half of the world population, despite that most infections are asymptomatic; some infections can develop chronic gastritis, peptic ulcer and gastric cancer. The aims of the study are the molecular detection of H. pylori and the main virulence factors association with clinical outcome of H. pylori infection. This study was start from February to September 2016, ninety two cases of H. pylori infections were detect in patients admitted to Medical Marjan City in Babylon -Iraq. The study display the high frequencies of H. pylori were observed for chronic gastritis, which h constituted 88% while low frequencies were 3.3% for gastric cancer whereas 8.7% for duodenal ulcer. Moreover, identification of H. pylori by PCR technique was performed on all gastric biopsy and ure C as well as ure genes were used as markers for confirmatory diagnosis of H. pylori through using specific primers of PCR technique. The result showed that, 84.8% and 73.9% of H. pylori were positive respectively for both genes. In additions, cag A gene was investigated in all H. pylori isolates. The result showed that65 (70.6%) was positive for PCR amplification of cag A gene whereas 56 (60.8%) was positive for PCR amplification of cag E gene. The frequency of the vac a gene found in the present study was 68.5% (63/92).It was concluded that the molecular detection of H. pylori genotype is important tool to determine pathogen city of H. pylori.Keywords: Helicobacter pylori, Gastric biopsy, Gastric diseases, Ure A gene, Ure C gene, Virulence genes.